2022
DOI: 10.3389/fbioe.2022.900644
|View full text |Cite
|
Sign up to set email alerts
|

A New Definition for Intracranial Compliance to Evaluate Adult Hydrocephalus After Shunting

Abstract: The clinical application of intracranial compliance (ICC), ∆V/∆P, as one of the most critical indexes for hydrocephalus evaluation was demonstrated previously. We suggest a new definition for the concept of ICC (long-term ICC) where there is a longer amount of elapsed time (up to 18 months after shunting) between the measurement of two values (V1 and V2 or P1 and P2). The head images of 15 adult patients with communicating hydrocephalus were provided with nine sets of imaging in nine stages: prior to shunting,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 72 publications
4
23
0
Order By: Relevance
“…Recently we showed that an important aspect of experimental assessment of hydrocephalic brain is the issue of the length of time that brain tissue is under elevated ICP 42 . This is a parameter that has been poorly studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently we showed that an important aspect of experimental assessment of hydrocephalic brain is the issue of the length of time that brain tissue is under elevated ICP 42 . This is a parameter that has been poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…This is a parameter that has been poorly studied. Firstly, hydrocephalus is often not acute with many patients presenting having had raised ICP for extended periods of time 17 , 42 . To accurately model this, it would be important to have a model where increased pressure on the brain is maintained for a long time 42 .…”
Section: Introductionmentioning
confidence: 99%
“…Non-invasive monitoring of the intracranial fluid content, such as intracranial compliance using MRI, has become an emerging need for clinical use in various types of hydrocephalus [ 73 ]. In the previous paragraph ( Section 3.3 ), we discussed that the increased μs’ may be associated with brain edema [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we envision that the data presented in this report on a more specific marker gene like TRPV4 and MAPT in NPH can significantly improve the prior cases reporting misdiagnosis of either AD or NPH ( Joseph et al, 2006 ; Joseph et al, 2008 ; Lee et al, 2010 ; Shimada et al, 2011 ). Biomechanical aspects of intracranial compliance ( Gholampour et al, 2022 ) should also be considered in the future as well for NPH and AD biomarker studies.…”
Section: Discussionmentioning
confidence: 99%